Screaming at the ump - Vernick, Audrey (Clarion Books, Houghton Mifflin Harcourt, 2014)
Twelve-year-old Casey lives with his father and grandfather at their family-run umpire school, and as he deals with middle school and his mother's unwelcome return, he stumbles on a sensational story that has him questioning his dream of becoming a journalist.